Neck pounding during sinus rhythm: a new clinical manifestation of dual atrioventricular nodal pathways. Issue 5 (1st May 1998) - Geelen, P; Primo, J; Brugada, J; Andries, E; Brugada, P
Abstract : Objective: To determine the clinical and electrophysiological characteristics of patients with paroxysmal palpitations and neck pounding during sinus rhythm. Methods: Clinical, electrocardiographic, and electrophysiological characteristics of six patients with paroxysmal palpitations and neck pounding during sinus rhythm were studied in basal conditions and when symptomatic. Response to treatment was observed. Results: Baseline ECGs were normal (four patients) or had first degree atrioventricular block with intermittent PR shortening. During symptoms, narrow QRS rhythms were seen without visible P waves (three patients) or with P waves partially hidden in the QRS complex (three patients). Dual atrioventricular nodal pathways were found in all five patients who had electrophysiological studies. In these patients the slow pathway conduction time was long enough (mean (SD), 425 (121) ms) for ventricular activation after slow pathway conduction during sinus rhythm to coincide with the next atrial depolarisation, causing neck pounding during exercise (four patients) or at rest (two patients). Tachycardia was not induced in any patient. Medical treatment aggravated symptoms in three patients. A pacemaker was successfully used in two. Conclusions: Neck pounding during sinus rhythm is a clinical manifestation of dual atrioventricular nodal pathways. Medical treatment may aggravate symptoms but a pacemaker may offer definitive relief.